Crowdsourced land rights - McLaren, Robin; Handja, Georges Thierry (Technical Centre for Agricultural and Rural Cooperation, 2012)
Crowdsourcing initiatives can encourage and support citizens to directly capture and maintain information about land rights. A database of crowdsourced land rights can improve security of tenure for the poorest